Women’s Voices in a Male World: Actions, Bodies, and Spaces Among the Ancient Maya - Elisa Perego (Papers from the Institute of Archaeology, 2007)
Feminist archaeology has prompted scholars to reconsider gender roles in ancient Mesoamerica.Current research, however, tends to focus on elite women, classes and sites. Although I do not ignore the potential of these sources, in this paper I am mainly concerned with issues such as the phenomenology of bodies and spaces, subroyal ritual actions, and daily activities such as cooking and weaving. My aim is to offer an overview of the most recent studies on gender in Maya archaeology and to provide ideas for further research by emphasising the need to engender ritual and individuate female discourses in the archaeological record.